2020
DOI: 10.1186/s13018-020-01899-w
|View full text |Cite
|
Sign up to set email alerts
|

Impingement-free hip range of motion after osteochondroplasty and relative neck lengthening in adults with healed Perthes disease

Abstract: Objective: Our main objective is to assess the efficiency of the osteochondroplasty with relative neck lengthening in adults with healed Perthes clinically (through assessment of impingement-free hip ROM, functional scores) and radiographically. Patients and methods: This was a prospective case series study included 30 hips of 30 patients who underwent osteochondroplasty and RNL due to symptomatic healed LCPD. This study included 16 males (53.3%) and 14 females (46.7%). The age of patients ranged from 19 to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…Although surgical failure was defined only as conversion to THA (4 hips, 15%), clinical failure was reported for 5 (18.5%) on the basis of a modified Harris hip score of <70 points, resulting in a combined failure of 33% in that study. In our study, only 2 (15%) of the patients had undergone a THA at the time of follow-up, similar to the rates of conversion to THA of between 7% to 15% found in previous studies 10,13,14,[28][29][30] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although surgical failure was defined only as conversion to THA (4 hips, 15%), clinical failure was reported for 5 (18.5%) on the basis of a modified Harris hip score of <70 points, resulting in a combined failure of 33% in that study. In our study, only 2 (15%) of the patients had undergone a THA at the time of follow-up, similar to the rates of conversion to THA of between 7% to 15% found in previous studies 10,13,14,[28][29][30] .…”
Section: Discussionsupporting
confidence: 90%
“…Our findings showed that, at a median of 10 years after surgery, patients with symptomatic residual LCPD deformity with preserved hips experienced a significant improvement in the WOMAC pain and stiffness scores but not in the WOMAC score for function in daily activities. The lack of improvement in WOMAC function was unexpected, as most previous studies have reported increased function in activities of daily living after SHD for LCPD 9,10,14,[27][28][29] . A previous study pointed out that one of the limitations of the WOMAC is that a patient's WOMAC score does not necessarily align with the patient's perception of their level of dysfunction 14 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To the best of the authors’ knowledge, no comparative studies directly compared the clinical outcomes of RFNL versus FHRO. However, their results were in line with recent reports showing a significant improvement in hip function, ROM, and postoperative pain following RFNL and FHRO 17,27. The authors recommend interpreting those results cautiously because the follow-up duration within the studies was limited.…”
Section: Discussionsupporting
confidence: 86%
“…However, their results were in line with recent reports showing a significant improvement in hip function, ROM, and postoperative pain following RFNL and FHRO. 17,27 The authors recommend interpreting those results cautiously because the follow-up duration within the studies was limited. A sufficiently long follow-up is crucial to ensure the continuity of the excellent early results and determine whether these procedures will alter the natural history of the disease.…”
Section: Discussionmentioning
confidence: 99%